Computation, wiring, and plasticity in synaptic clusters. (October 2021) - Pulikkottil, Vinu Varghese; Somashekar, Bhanu Priya; Bhalla, Upinder S.
Abstract: Synaptic clusters on dendrites are extraordinarily compact computational building blocks. They contribute to key local computations through biophysical and biochemical signaling that utilizes convergence in space and time as an organizing principle. However, these computations can only arise in very special contexts. Dendritic cluster computations, their highly organized input connectivity, and the mechanisms for their formation are closely linked, yet these have not been analyzed as parts of a single process. Here, we examine these linkages. The sheer density of axonal and dendritic arborizations means that there are far more potential connections (close enough for a spine to reach an axon) than actual ones. We see how dendritic clusters draw upon electrical, chemical, and mechano–chemical signaling to implement the rules for formation of connections and subsequent computations. Crucially, the same mechanisms that underlie their functions also underlie their formation. Graphical abstract: Image 1 Highlights: Clustered synaptic inputs subserve key dendritic computations including correlation detection and sequence discrimination. Multiple kinds of spatial signaling, including electrical, chemical and mechano-chemical, underlie these computations. Clustered computation requires convergent input with temporally organized activity. Mechano-chemical signaling and spatio-temporal learning rules select for inputs relevant to dendritic computation. The processes that govern cluster computation and cluster formation have much in common.